2002
DOI: 10.1161/hh0402.105898
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 Transcription Factor as a Molecular Target for Nitric Oxide– and Cyclic Nucleotide–Mediated Suppression of cGMP-Dependent Protein Kinase-Iα Expression in Vascular Smooth Muscle Cells

Abstract: Abstract-cGMP-dependent protein kinase (PKG) expression is highly variable and decreases in cultured vascular smooth muscle cells (VSMCs), exposure of cells to nitric oxide (NO), or in response to balloon catheter injury in vivo. In this study, the mechanisms of human type I PKG-␣ (PKG-I␣) gene expression were examined. Three structurally unrelated NO donors decreased PKG-I␣ promoter activity after transfection of a promoter/luciferase construct in VSMCs. Promoter deletion analysis demonstrated that (1) a 120-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 39 publications
6
44
1
Order By: Relevance
“…In the NO/sGC signaling pathways, Sp1 is important for the basal activity of endothelial (Wu 2002) and neuronal (Saur et al 2002, Bachir et al 2003 NO synthases. Moreover, it is also involved in the regulation of human type I protein kinase G gene expression (Sellak et al 2002). Together with the findings presented here, these observations indicated the importance of Sp1 in the NO/sGC signaling.…”
Section: Discussionsupporting
confidence: 87%
“…In the NO/sGC signaling pathways, Sp1 is important for the basal activity of endothelial (Wu 2002) and neuronal (Saur et al 2002, Bachir et al 2003 NO synthases. Moreover, it is also involved in the regulation of human type I protein kinase G gene expression (Sellak et al 2002). Together with the findings presented here, these observations indicated the importance of Sp1 in the NO/sGC signaling.…”
Section: Discussionsupporting
confidence: 87%
“…Its expression is differently regulated in tumors and in normal tissue (14,43,44). In mammalian cells, two different genes encode type I and II PKGs (45).…”
Section: Discussionmentioning
confidence: 99%
“…Various Sp1 phosphorylations have been documented to increase both Sp1 binding to GC-box and transactivation activity; these include serine phosphorylation by protein kinase C-␥ (PKC-␥), 21 Ser 59 phosphorylation by cyclin A-dependent kinase 2, 25 as well as Thr 453 and Thr 739 phosphorylation by p42/p44 26 Furthermore, Sp1 also has been shown to undergo phosphorylation by PKA 27,28 ; however, although this phosphorylation increased its GC-box binding, it converted Sp1 to a repressor of gene expression. This is consistent with studies in which certain phosphorylations conferred upon Sp1 a transcriptional repression activity.…”
Section: Discussionmentioning
confidence: 99%
“…24 Whereas various Sp1 phosphorylations have been documented to increase its DNA binding and transactivation activity, 21,25,26 a few reports suggested that certain phosphorylations compromise Sp1 binding and transactivation activity. 17,18 Furthermore, Sp1 has been shown to undergo phosphorylation by cAMP-dependent protein kinase (PKA), 27,28 in which case the phosphorylation increased its GC-box-binding capability but rendered it a repressor of gene expression. Consistently, alternative phosphorylations also have been reported to render Sp1 a transcriptional repressor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation